Career Entry Strategy — A Systematic Approach - Clark, Andrew K. (Canadian Journal of Counselling and Psychotherapy, 2012)
A career entry program for adolescents entering the work force is described. The 12-step procedure is organized in four phases: Preliminary; Resume; Search; and Interview.